Supply of Credit Investigation into Micro and Small Enterprises in the Minas Gerais State: an approach by strategic groups - Santos, Lucas Maia dos; Ferreira, Marco Aurélio Marques; Abrantes, Luiz Antonio; Silveira, Suely de Fátima Ramos (Review of Business Management, 2009)
Despite the evident increase of the microcredit supply in Brazil and Minas Gerais State, there is a need for knowledge on the fundamental aspects of the maintenance and incentive to this initiative. So, this work was conducted to identify and analyze characteristics of strategic groups in the supplying credit institutions, by summarizing the profile of those institutions under the viewpoint of the productive microcredit premises suppositions considering the Minas Gerais State as reference. This was an exploratory and descriptive research with both quantitative and qualitative approach, including 81 supplying credit institutions. The factorial analysis followed by cluster analysis of these institutions made it possible the identification of the following groups showing different characteristics concerning to propagation of the credit for MPEs: Focused, Dispersed and Defocused. The results showed that only 9% suppliers grant advantages to MPEs, relative to the microcredit application methodologies. On the other hand, it is well known that most institutions in the area under study do not grant specific advantages to MPEs, and those ones infrequently appeal to the credit operations, therefore prejudicing the development of this sector, as considering the asymmetry between the supply and demand of the microcredit. Key words: Strategic groups. Microcredit. Micro and small enterprises. Cluster.